Relationship between stress and lifestyle with internet addiction among Z generation/ Normaizatul Akma Saidi ... [et al.] - Saidi, Normaizatul Akma; Ab Ghaffar, Siti Fatimah; Chua, Yee Sa; Ezani, Nur Nabila; Abdul Zhani, Nor Shuhada; Singh, Taranjit Kaur Ram (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
Although the internet has resulted in substantial benefits under the fourth industrial revolution (specifically regarding knowledge, interaction, and social communication), internet addiction is currently a public health conundrum following severe and uncontrolled internet utilisation. This research designed to identify the substantial factors connected to internet addiction. A cross-sectional analysis was performed among the Z generation in Malaysia. Summarily, 384 respondents were selected in this research with the convenience sampling technique. A set of self-reported questionnaires were also distributed for data gathering. Notably, Pearson correlation and multiple linear regression were utilised for univariate and multivariate analyses. The study assessments were performed with a 95% confidence interval (CI) and significance level at p < 0.05. Most respondents were Chinese (44.5%), males (56.8%), degree holders (59.4%), and students (41.4%). Under the multivariate analysis, stress (p < 0.001) and lifestyle (p < 0.001) denoted the significant factors related to internet addiction while depression and anxiety were statistically insignificant (p > 0.05). In conclusion, stress and lifestyle proved vital in forecasting internet addiction among the Z generation in Malaysia. Internet addiction intervention program for Z generation could be developed by managing stress and lifestyle.